Effects of abrupt changes in the Atlantic meridional overturning circulation over the Amazon Basin: an isotopic and elemental approach - Crivellari, Stefano (2018)
One of the most important finding emerging from paleoclimate research of the last 20 years is the fact that global climate has the potential to abruptly switch between states. Gradual changes in climate during the last 50 ka are punctuated by fast transitions whose onsets occurred within a few decades. These abrupt climatic changes are probably the closest analogues to the pace of modern climate change. It is well established that abrupt climate changes during late Quaternary are associated to severe reorganization of the atmospheric and oceanic circulations. In this thesis we attempt to advance the understanding of the context in which natural forcing lead to abrupt climate change. This is of paramount importance in order to provide a solid framework for understanding modern climate change and actualize effective mitigation policies. A key component of the global climate system is the Atlantic Meridional Overturning Circulation (AMOC). The AMOC is responsible for the transport of heat and salt to the high latitudes of the North Atlantic. A deviation from the equilibrium state in the rate of the AMOC flow is associated to severe reorganization of atmospheric and oceanic circulation which is undoubtedly a fundamental mechanism used for explaining abrupt climate change. A decrease in the export of heat to the northern hemisphere causes a steeper latitudinal sea surface temperature (SST) gradient in that hemisphere intensifying the northeastern trade winds. This, in turn, has a direct effect on tropical South American precipitation as more moisture from the adjacent ocean is brought into the continent. Sites located at the western tropical Atlantic Ocean are sensitive to both changes in continental hydrology as well as regional oceanography. Therefore, they represent ideal targets for paleo-records and an opportunity for paleoclimate reconstructions. A well dated sediment core (i.e., GeoB16224-1), collected 400 km to the north of the Amazon River mouth off French Guiana (7° N) was retrieved and analysed at high resolution with a multitude of paleo-proxies. The core site is located under the full influence of the Amazon River discharge, offering for the first time a basin-wide integrated record of past changes in Amazonian hydrology. We targeted the last glacial-interglacial transition as well as abrupt millennial-scale climatic changes of the late Pleistocene (last 45 ka). We were able to obtain on the one hand relevant information on the hydrological history of the Amazon Basin and the regional changes in marine properties with special emphasis on Heinrich Stadial (HS) 1 (about 18 to 15 cal ka BP, Chapter 2), Dansgaard-Oeschger Stadials (DOS) 8 to 5 (about 37 to 31 cal ka BP, Chapter 3), and on the other hand relevant information on the thermal history of the upper water column in the western tropical Atlantic for the last 45 ka (Chapter 4), resolving important discrepancies in previously published records. Thus, the main objectives of this thesis were: (i) to investigate the internal structure of HS1 and its effect on Amazonian hydrology at high resolution; (ii) to investigate the different impact of HS and DOS on precipitation within the Amazon Basin; and (iii) to understand the thermal evolution of the upper water column in the western tropical Atlantic during the last 45 ka with emphasis on millennial-scale anomalies. We first explored the relationship between HS 1 and Amazonian hydroclimate. We present a high resolution multiproxy study based on samples from gravity core GeoB16224- 1. We reconstructed surface water hydrography using oxygen stable isotopes (d18O) and Mg/Ca-derived paleotemperatures from planktonic foraminifera Globigerinoides ruber, as well as salinity based on stable hydrogen isotopes (dD) of palmitic acid. We also analysed branched and isoprenoid tetraether (BIT) concentrations and compared them to existing records of bulk sediment ln(Fe/Ca) data and vegetation reconstruction based on stable carbon isotopes from n-alkanes, in order to understand the relationship between continental precipitation, changes in vegetation and sediment production. Our results indicate a twophased HS1 (HS1a and HS1b). During HS1a (18-16.9 cal ka BP), a first sudden increase in SST in the western tropical Atlantic correlated with the slowdown of the AMOC and the associated southern hemisphere warming phase of the bipolar seesaw. This phase was also characterized by an increased delivery of terrestrial material. During HS1b (16.9-14.8 cal ka BP), a decrease in terrestrial input was, however, associated with a marked decline of seawater d18 O (d18Osw) and palmitic acid dD. Both isotopic proxies independently indicate a drop in sea surface salinity (SSS). Our records thus suggest that the expected increase in SSS due to the AMOC slowdown was overridden by a two-phased positive precipitation anomaly in Amazonian hydroclimate. Moreover, progressively lower values of ln(Fe/Ca) and BIT index values coincident with depleted d18Osw during HS1b might suggest a shift in the main locus of precipitation within tropical South America towards regions less affected by erosion (i.e., Amazonian Plain and Brazilian Shields). Consequently, we were interested in understanding the different impact of HS-type from DOS-type climatic events in Amazonian hydrology. Older sections of the same marine sediment core were therefore investigated for ln(Fe/Ca), alkenone C37 and carbonate fragmentation index, and compared with previously published continental paleo-records across different latitudes of the tropical Americas. A discernible difference in the effect of HS is appreciable when compared to DOS-type of millennial-scale climatic events. We find that northeastern Brazilian precipitation experienced significant increases during HS but was characterized by only subtle changes during DOS. This is associated with the degree of the Intertropical Convergent Zone dislocation caused by a reduction in the strength of the AMOC. Finally, we found the need to better characterize the actual thermal behaviour of the upper water column at the western tropical Atlantic for the last 45 ka. We therefore performed a multiproxy, high resolution temperature reconstruction from marine sediment core GeoB16224-1, which is based on Mg/Ca on G. ruber, alkenone unsaturation index Uk\'37, TEX86, and the modern analogue technique (MAT) applied to planktonic foraminifera assemblages. We detected positive temperatures anomalies during slowdown events of the AMOC HS4-HS1, as our Mg/Ca-derived SST and TEX86 clearly show. Positive SST anomalies in our Mg/Ca record coincide with Antarctic isotope maxima (AIM)12 to AIM1 from the EPICA Dronning Maud Land ice core ?18O record. Nevertheless, UK\'37 and MAT (50 m) temperature reconstruction on GeoB16224-1 show negative anomalies during HS3 and HS1. We infer that whereas TEX86 and Mg/Ca respond to surface temperatures, UK\'37 and MAT (50 m) are affected by subsurface temperature variations which respond to vertical movement of the thermocline. The presence of ITCZ related precipitation is the most likely responsible for the increased stratification and consequent shoaling of the thermocline. Nevertheless important non-thermal physiological effects on the alkenone export has also to be taken into account. The presence of low SSS and large amount of suspended particulate related to the Amazon River increased discharge might imprint a negative temperature bias on the UK\'37. However, this alone is unlikely to explain the entire variability in the UK\'37 temperature signal.